2009
DOI: 10.1590/s1516-35982009000600017
|View full text |Cite
|
Sign up to set email alerts
|

Consumo e digestibilidade dos nutrientes em cabras Moxotó recebendo dietas com diferentes níveis de feno de maniçoba

Abstract: RESUMO -Objetivou-se com este trabalho avaliar a utilização do feno de maniçoba (Manihot glaziovii Muell. Arg.) em diferentes níveis (30, 40, 50 e 60%) sobre os consumos e as digestibilidades de matéria seca (MS), matéria orgânica (MO), proteína bruta (PB), energia bruta (EB), extrato etéreo (EE), carboidratos totais (CT), carboidratos não-fibrosos (CNF), fibra em detergente neutro (FDN) e fibra em detergente ácido (FDA) e os consumos de água e nutrientes digestíveis totais (NDT). Utilizaram-se oito cabras da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
3
2
0
3
Order By: Relevance
“…Araújo et al (2009) observed that the dry extract is directly related to the production of milk solids and thus follows the same pattern observed for these variables.…”
Section: Resultssupporting
confidence: 70%
“…Araújo et al (2009) observed that the dry extract is directly related to the production of milk solids and thus follows the same pattern observed for these variables.…”
Section: Resultssupporting
confidence: 70%
“…For the quantification of fibrous fractions -neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose, cellulose and lignin, the sequential method described by Van Soest et al (1991), with Ankon Fiber Analyzer equipment was used, with polyester bags (non-woven textile, TNT), weight 100 mm (Araújo et al, 2009). Prior to determining the fibrous fractions, the samples were defatted by the Soxlet method, and the yields of ethereal extract samples were obtained by the same method (Komarek, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the amount of fodder, the quality also oscillates over time, which makes it difficult to define food programs. A strategy used in the dry season for dairy goat is the intensification in the production model with the collection of animals to management centers or small areas for the most suitable feeding, allowing even rest in the pasture areas, and sustainable management of the caatinga ecosystem (Araújo, Medeiros, Carvalho, Silva, & Chagas, 2009).…”
Section: Introductionmentioning
confidence: 99%